2016
DOI: 10.1002/aic.15339
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ga doping on Pt/CeO2‐Al2O3 catalysts for propane dehydrogenation

Abstract: This paper describes catalytic consequencesThis paper describes catalytic consequences of Pt/CeO 2 -Al 2 O 3 catalysts promoted with Ga species for propane dehydrogenation. A series of PtGa/CeO 2 -Al 2 O 3 catalysts were prepared by a sequential impregnation method. The as-prepared catalysts were characterized employing N 2 adsorption-desorption, X-ray diffrtaction, temperature programmed reduction, O 2 volumetric chemisorption, H 2 -O 2 titration, and transmission electron microscopy. We have shown that Ga 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 68 publications
0
62
0
Order By: Relevance
“…Then, a mixture of 28 vol % propane and 28 vol % H 2 in N 2 was fed at a rate of 25 mL/min. The weight hourly space velocity (WHSV) of propane was 3 h −1 , which was generally used in relevant studies . Exhaust streams were analyzed using an online GC (2060) equipped with a flame ionization detector (Chromosorb 102 column) and a thermal conductivity detector (Al 2 O 3 Plot column).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, a mixture of 28 vol % propane and 28 vol % H 2 in N 2 was fed at a rate of 25 mL/min. The weight hourly space velocity (WHSV) of propane was 3 h −1 , which was generally used in relevant studies . Exhaust streams were analyzed using an online GC (2060) equipped with a flame ionization detector (Chromosorb 102 column) and a thermal conductivity detector (Al 2 O 3 Plot column).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, growing production of shale gas drives the price of propane down, which makes the propane dehydrogenation (PDH) process commercially attractive for propylene production . Pt and CrO x are generally used as catalytically active materials in industrial PDH processes and they were extensively investigated . However, the high cost of Pt and the hypertoxicity of CrO x somehow restrict the development of PDH industry.…”
Section: Introductionmentioning
confidence: 99%
“…Thei ntensities of the XRD peaks corresponding to Pt were very weak owing to the low loading (0.8 wt %b yI CP). [12] Thep ore size and Brunauer-Emmett-Te ller (BET) surface area of the PTIM-MSs were determined to be 5.3 nm (average pore size) and 288 m 2 g À1 ,respectively, by nitrogen adsorption measurements (Figure S6 b). These results indicate am esoporous structure,w hich allows for the penetration and transportation of reactants and products.…”
mentioning
confidence: 99%
“…In addition, the electronic structures also change after the substitution of the Al atoms by the Fe atoms on the surface. Except for the incorporation of Fe into the alumina surface, the B and Ga atoms, which are often used as the trivalent substitution ions for the zeolites [15,16], are also used in experiments for the preparation of high performance catalysis and semiconductors [8,9,[17][18][19]. Kibar et al prepared nanostructured boron doped alumina catalyst support [20] and found that the morphology of the supports can be modified from cracked surface to nanosphere formation by the introduction of boron.…”
Section: +mentioning
confidence: 99%
“…In order to improve the performance of the material, some heteroatoms were usually chosen to be incorporated into the -alumina bulk and surfaces [8,9]. For example, the Fe atom was usually used to improve the catalytic performance of -alumina [10].…”
Section: Introductionmentioning
confidence: 99%